Alkynes and Nitrogen Compounds: Useful Substrates for the Synthesis of Pyrazoles. Issue 37 (11th May 2020) - Neto, Jose S. S.; Zeni, Gilson
Abstract: The easy preparation and functionalization of pyrazoles associated with their innumerable biological properties have made this class of N‐heterocycles very attractive for the development of new synthetic routes and applications. The cyclization reactions of alkynes and nitrogen compounds represent a powerful tool for the preparation of pyrazoles. This Review covers the recent advances in the preparation of pyrazoles by reacting alkynes and nitrogen compounds under transition‐metal‐catalyzed or metal‐free conditions. Abstract : One goal : Cyclization reactions of alkynes and nitrogen compounds represent a powerful tool for the preparation of pyrazoles. This Review covers the recent advances in the preparation of pyrazoles starting from alkynes and nitrogen compounds by using transition‐metal‐catalyzed or metal‐free conditions to promote the cyclization.